Active stewardship in healthcare: Lessons from China's health policy reforms. (22nd June 2022) - He, Alex Jingwei; Bali, Azad Singh; Ramesh, M.
Abstract: Governments across the globe have made repeated attempts to reform their health systems in recent decades with the purpose of improving access while containing costs. What is the role of government in contemporary health policy in achieving these somewhat contradictory goals? This paper conceptualises this role as one of "active stewardship" wherein the government is a central actor steering and coordinating the sector through a portfolio of diverse policy tools. In this conceptualisation, the government is not a passive participant—in merely financing, delivering, or regulating the sector—but a steersman at the helm that sets policy objectives and actively pursues them. We argue that active stewardship is central to achieving contemporary health policy priorities of universal healthcare. We apply this conceptualisation to China's recent healthcare forms and show that the role of the government in governing the sector has changed substantially over time, particularly since 2009, and the changes are showing promising results. China's experience suggests that governments need to more actively guide and shape the behaviour of both public and private players in order to achieve the goals of universal health coverage. It also suggests that a high degree of policy capacity is essential if active stewardship is to be effective.